Estudos químicos dos compostos heterocíclicos mesoiônicos e sua potencialidade antifúngica. - Souza, Helivaldo Diogenes da Silva (2012)
Heterocyclic compounds like mesoionics are flat and nonaromatic betaínes stabilized by electron delocalization. Some of their properties enable these compounds to be used in crystal liquid field, nonlinear optics and development of new drugs since betaínes possess a broad spectrum of biological activities such as antibacterial, antitumor, antifungal, antimalarial, anticonvulsant, etc. The aim of this work was the synthesis and characterization of the following mesoionic compounds 1,3-thiazolium-5- thiolate class in free base form (MI-H1.1, MI-H1.2, MI-H1.3) and derivates as S-methylated and S-ethylated salts (MI-H2.1, MI-H2.2, MIH2.3, MI-H2.4, MI-H2.5 e MI-H2.6) and of the mesoionic compounds 1,3-diazolio-5-thiolate class in free base form (MI-H4.1, MI-H4.2, MIH4.3 e MI-H4.4) and derivates as S-ethylated salts (MI-H5.1, MI-H5.2 e MI-H5.3). These compounds were properly characterized by spectroscopic techniques such as IR, 1H and 13C NMR. The compounds MI-H1.1, MIH1.2, M1-H2.2, MI-H2.5, MI-H3.2 e MI-H3.4 tested to antifungal activity and the results showed the four of the present activity to inhibit five of six Candidum species with MIC in the range of 64 μg/mL.